PENGARUH KOMPETENSI GURU AKIDAH AHLAK, POLA ASUH ORANG TUA DAN MEDIA BERBASIS TEKNOLOGI TERHADAP MOTIVASI BELAJAR SISWA DI MAN 1 KABUPATEN SUKABUMI: The Integration of Parenting Styles and Digital-Based Learning Innovations in Enhancing Student Learning Motivation at Madrasah Aliyah - Rusli Hamdani, Mohammad; Rifaie, Muhammad Mukrim Faer; Yasir, Muhamad; Erihadiana, Mohamad; Haryanti, Erni (Perkumpulan Peneliti dan Pegiat Literasi, 2025)
The advancement of digital technology has transformed educational paradigms, including strategies to enhance students' learning motivation. However, the effectiveness of digital learning largely depends on environmental support, particularly parental involvement. This study aims to explore how the integration of parenting styles and digital learning innovations contributes to students' learning motivation in Madrasah Aliyah. This research employs a qualitative approach with a case study method involving in-depth interviews, participatory observations, and document analysis. The findings reveal that authoritative parenting fosters disciplined learning habits and optimal utilization of digital technology, whereas permissive parenting often leads to student distraction by digital entertainment. Furthermore, interactive digital learning media, such as YouTube and quiz applications, prove more effective in engaging students and enhancing comprehension than conventional learning methods. However, technological access limitations and insufficient digital literacy among parents and educators remain significant barriers to implementing digital-based learning. Therefore, synergy among families, schools, and educational policies is essential in creating an inclusive and technology-oriented learning ecosystem. The implications of this study highlight the necessity of improving digital literacy for parents and teachers and enhancing technological infrastructure to support the effectiveness of digital learning.